2017
DOI: 10.1158/1078-0432.ccr-16-0738
|View full text |Cite
|
Sign up to set email alerts
|

18F-fluoromisonidazole PET and Activity of Neoadjuvant Nintedanib in Early HER2-Negative Breast Cancer: A Window-of-Opportunity Randomized Trial

Abstract: Purpose: We previously detected promising efficacy of neoadjuvant nintedanib (a multityrosine kinase inhibitor, TKI) in early HER2-negative breast cancer. In a preclinical study, we monitored stromal hypoxia with 18 F-fluoromisonidazole-positron emission tomography (18F-FMISO-PET); we found that reoxygenation of tumors (or lack of it) during a window-ofopportunity (WoO) treatment with TKIs correlated with the benefit (or lack of it) from TKI-plus-chemotherapy combinations. We studied the predictive role of 18F… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 41 publications
(43 reference statements)
3
34
0
Order By: Relevance
“…Later studies revealed that cediranib transiently increases perfusion and oxygenation in the subset of glioblastoma patients that survive longer (3133). Similar findings of increased vessel function and oxygenation associating with pathological response and outcome have been reported with nintedanib (34), eribulin (35), and bevacizumab (3538) in breast cancer (BC) patients. While perfusion was reduced by bevacizumab in the overall patient cohort of non-small-cell lung cancer (NSCLC) patients, increased perfusion after bevacizumab treatment was associated with improved overall survival (39).…”
Section: Oxygenation Is the Critical Biomarker For Patient Outcomes Asupporting
confidence: 71%
“…Later studies revealed that cediranib transiently increases perfusion and oxygenation in the subset of glioblastoma patients that survive longer (3133). Similar findings of increased vessel function and oxygenation associating with pathological response and outcome have been reported with nintedanib (34), eribulin (35), and bevacizumab (3538) in breast cancer (BC) patients. While perfusion was reduced by bevacizumab in the overall patient cohort of non-small-cell lung cancer (NSCLC) patients, increased perfusion after bevacizumab treatment was associated with improved overall survival (39).…”
Section: Oxygenation Is the Critical Biomarker For Patient Outcomes Asupporting
confidence: 71%
“…The clinical application of hypoxia imaging has provided essential information on tumor microenvironmental biology, adding to information on tumor size, growth factor receptors, and cellular proliferation. Hypoxia imaging may enable tailoring therapeutic strategies based on baseline risk assessment [ 26 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…So far, the RCB score has only been used to a limited extent by independent researchers outside of the MD Anderson Cancer Center. 15,27,[33][34][35][36] In the following study, we investigated the prognostic impact of the RCB score with special emphasis on RFS in a breast cancer collective treated at a single oncology unit and analyzed at a single pathology department.…”
mentioning
confidence: 99%